Human Moral Becoming and the Surrealist Imagination: Saulius Tomas Kondrotas and Šarūnas Sauka - Vedrickaitė, Imelda (Colloquia, 2017)
The author of this article interprets the surrealist narratives of Saulius Tomas Kondrotas and Šarūnas Sauka as signs of both a crumbling empire and the rebirth of human dignity in late Soviet-era literature and art. A sense of epochal shift provides a common background of allegorical narration in both Kondrotas’s and Saukas’s narratives, protecting them from flat politicising and encouraging us to read their work as an encounter between the human and the eternal. Countering Soviet values, Kondrotas and Sauka place the universal rebellion of the artist against an ideology that imprisons the individual at the core of their work, making it possible to draw a connection to the imagination of the medieval alchemist, as they too concentrate their attention on the search for God and the resulting visions-projections. Kondrotas’s and Saukas’s works are characterised by oniric, surrealist stylistics, an understanding of the world as a dangerous place, and the human-godlike-animal matrix. The end of the world, the collapse of foundational hierarchies of values, and a feeling of moral ambivalence are common to both, leading them to search for solutions in response to human moral decline. Kondrotas and Sauka both speak about human rebirth, one of the oldest of human archetypes and one central to the alchemical imagination.